ANXIETY AND DEPRESSION IN TIMES OF PANDEMIC BY COVID 19 - Vera Calmet Velia Graciela; Aguilar Armas Haydee Mercedes; Flores Ledesma Katia Ninoska; Javier Alva Leda (PalArch's Journal of Archaeology of Egypt / Egyptology, 2021)
The present study reveals the emotional reactions of anxiety, depression, and their variants to the pandemic, which is why the relationship between anxiety and depression (chi of 75.667 and p <0.05) in times of the COVID-19 pandemic was determined, in addition the factors associated with these variables were identified. We worked with a sample of 619 people from the city of Trujillo-Peru, using a non-probability sampling for convenience. The Goldberg Anxiety and Depression scales were used, with adequate validity and reliability; accompanied by a sociodemographic file. Finding that anxiety is more prevalent than depression, likewise the associated factors are female sex, the age group of young people and adolescents, economic and working conditions.